2019
DOI: 10.1186/s13012-019-0934-y
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of a care bundle for fever, hyperglycaemia and swallow management in a National Audit for acute stroke: evidence of upscale and spread

Abstract: Background In the Quality in Acute Stroke Care (QASC) trial undertaken in stroke units (SUs) located in New South Wales (NSW), Australia (2005–2010), facilitated implementation of a nurse-led care bundle to manage fever, hyperglycaemia and swallowing (FeSS protocols) reduced death and disability for patients with stroke. We aimed to determine subsequent adherence to the bundled FeSS processes (reflective of the protocols) between 2013 and 2017 in Australian hospitals, and examine whether changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Uniform and standardized care for stroke patients has been shown to reduce LOS, decrease rate of DCI, and positively affect patient functional outcomes at 90 days. 243,244,246,247,249,250 Nursing interventions are often driven by stepwise algorithms and protocols that clearly define the activities. The QASC trial (Quality in Acute Stroke Care), a large observational study, found that patients in a nurse-initiated intervention group using a fevers, sugars, and swallowing protocol had a 16% absolute improvement in death and dependency at 90 days compared with patients in the control group.…”
Section: 1 Nursing Interventions and Activitiesmentioning
confidence: 99%
“…Uniform and standardized care for stroke patients has been shown to reduce LOS, decrease rate of DCI, and positively affect patient functional outcomes at 90 days. 243,244,246,247,249,250 Nursing interventions are often driven by stepwise algorithms and protocols that clearly define the activities. The QASC trial (Quality in Acute Stroke Care), a large observational study, found that patients in a nurse-initiated intervention group using a fevers, sugars, and swallowing protocol had a 16% absolute improvement in death and dependency at 90 days compared with patients in the control group.…”
Section: 1 Nursing Interventions and Activitiesmentioning
confidence: 99%
“…257 Hospitals with higher use of standardized order sets and adherence to specific pathways are associated with overall decreased complication rates related to infection, pneumonia, and hyperglycemia for patients with stroke. 259 2. The risk of death resulting from pneumonia for patients with stroke is ≈35%.…”
Section: Neurosurgical Intervention Can Alter the Clinicalmentioning
confidence: 99%
“…Initiation of standardized protocols on admission allows for early involvement of multidisciplinary team members and has been associated with decreased complication rates. 6…”
Section: Key Recommendations For the Hospitalistmentioning
confidence: 99%
“…The needs of ICH patients can be difficult to predict so patients should be transferred to a facility with neurosurgical and neuro‐specialized critical care capabilities. Initiation of standardized protocols on admission allows for early involvement of multidisciplinary team members and has been associated with decreased complication rates 6 …”
Section: Key Recommendations For the Hospitalistmentioning
confidence: 99%